(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The first Ethernet technology network was built on a 0.5-inch diameter. Later, a physical footprint for the Ethernet stand, which can be used in other different data transmission environments, was also discovered. The definition of the optional physical environment of the CSMA/CD memory method and the existing VAQT longitudinal Ethernet 10 Mbit/s technology remains the same.